2010
DOI: 10.3109/09638230802522999
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and mental health in the Royal Navy: A mixed methods paper

Abstract: Internal stigma remains a significant barrier to help seeking within the Royal Navy, especially for distressed personnel. This may be especially problematic for junior personnel who are known to be particularly vulnerable to developing mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 13 publications
2
35
2
Order By: Relevance
“…problematic, especially for junior personnel who are particularly vulnerable to developing mental health problem. 19 Stigma associated with mental health care and concerns about service utilization appearing on military records and on career advancement ranked high as barriers among service members. For families of soldiers, barriers included the costs of mental health care, trouble with scheduling appointments, difficulty in getting time off work, and not knowing where to get help.…”
Section: Resultsmentioning
confidence: 99%
“…problematic, especially for junior personnel who are particularly vulnerable to developing mental health problem. 19 Stigma associated with mental health care and concerns about service utilization appearing on military records and on career advancement ranked high as barriers among service members. For families of soldiers, barriers included the costs of mental health care, trouble with scheduling appointments, difficulty in getting time off work, and not knowing where to get help.…”
Section: Resultsmentioning
confidence: 99%
“…Those with mental health problems were much more likely to report barriers to care and concerns about stigmatisation than those who were well (Hoge 2004). In a study in the Royal Navy, distressed service personnel reported selfstigmatising beliefs two to three times more often than those who were not distressed (Langston 2009). Individuals with stress were also more sensitive to barriers of care and were less likely to believe that any help they might receive would be rendered confidentially (Langston 2009).…”
Section: Improving the Mental Health Of Ex-service Personnel And Resementioning
confidence: 99%
“…In a study in the Royal Navy, distressed service personnel reported selfstigmatising beliefs two to three times more often than those who were not distressed (Langston 2009). Individuals with stress were also more sensitive to barriers of care and were less likely to believe that any help they might receive would be rendered confidentially (Langston 2009). This may explain the finding by the charity Combat Stress that the average delay between symptom onset and presentation to services is 13 years for veterans (Combat Stress, personal communication 2007).…”
Section: Improving the Mental Health Of Ex-service Personnel And Resementioning
confidence: 99%
“…The purpose of screening for PTSD would be to improve the prognosis of the condition by the use of efficacious treatment, but identification of PTSD may not be helpful if a large proportion of cases can improve without treatment (Rona et al, 2005). This issue is also complicated by what is known about help seeking and stigma and only a proportion of personnel with PTSD will actually seek help (Ben-Zeev et al, 2012;Iversen et al, 2011;Langston et al, 2010).…”
Section: Trajectories Of Ptsdmentioning
confidence: 99%